Fatal intoxication caused by conventional-dose methotrexate in an elderly patient with end-stage renal disease - Qian He; Xu Huang (Medicine, 2026)
Rationale: Methotrexate (MTX) is a first-line agent for rheumatoid arthritis, and impaired renal excretion drastically elevates the risk of fatal drug accumulation. End-stage renal disease (ESRD) patients face an extreme toxicity risk even under conventional low-dose MTX, yet related fatal cases remain underreported. This case highlights critical clinical warnings for rheumatologists and emergency physicians. Patient concerns: A 71-year-old male with a 5-year history of rheumatoid arthritis and 1-year untreated chronic kidney disease stage 5 received weekly 10 mg subcutaneous MTX for 3 consecutive weeks without folic acid supplementation or regular laboratory monitoring. One day after his latest injection, he developed persistent nausea, vomiting, extensive oral ulcers, a skin rash, and drowsiness. Diagnoses: Severe MTX intoxication complicated by profound bone marrow suppression, septic shock, and multiple organ dysfunction syndrome. Persistently elevated serum MTX confirmed impaired renal drug clearance in ESRD. Interventions: Immediate MTX discontinuation, leucovorin calcium rescue, continuous renal replacement therapy, broad-spectrum anti-infection treatment, blood product transfusion, and invasive mechanical ventilation for progressive circulatory and respiratory failure. Outcomes: Serial serum MTX remained elevated 6 days after the final dose. Despite full intensive supportive care, the patient died of refractory septic shock and irreversible multiorgan failure. Lessons: Conventional-dose MTX is contraindicated for ESRD patients. Mandatory pre-prescription renal function assessment, regular laboratory monitoring, and folate supplementation are essential to prevent life-threatening MTX toxicity in high-risk elderly populations.